Non-animal glioblastoma models for personalized treatment - Alja Zottel; Ivana Jovčevska; Neja Šamec (Heliyon, 2023)
Glioblastoma is an extremely lethal cancer characterized by great heterogeneity at different molecular and cellular levels. As a result, treatment options have moved far from systemic and universal therapies toward targeted treatments and personalized medicine. However, for successful translation from preclinical studies to clinical trials, experiments must be performed on reliable disease models. Numerous experimental models have been developed for glioblastoma, ranging from simple 2D cell cultures to study the nature of the disease to complex 3D models such as neurospheres, organoids, tissue-slice cultures, bioprinted models, and tumor on chip, as perfect prototypes to evaluate the therapeutic potential of different drugs. The presence of multiple research models is consistent with the complexity and molecular diversity of glioblastoma. The advantage of such models is the recapitulation of the tumor environment, and in some cases the preservation of immune system components as well as the creation of simple vessels. There are also two case studies translating in vitro studies on glioblastoma organoids to patients as well as four ongoing clinical trials using glioblastoma models, indicating high clinical potential of glioblastoma models.